Improving location recommendations with temporal pattern extraction - Marinho, Leandro Balby; Nunes, Iury; Sandholm, Thomas; Nóbrega, Caio; Araújo, Jordão; Pires, Carlos Eduardo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2012)
A key challenge in mobile social media applications is how to present personalized content that is both geographically and temporally relevant. In this paper, we propose a new and generic temporal weighting function for improving location recommendations. First, we identify areas of interest to recommend by clustering geographic activity based on a trace of geotagged photos. Next, the clusters are temporally weighted using TF-IDF, in order to capture seasonality, and a decay scoring function to capture preference drift. Finally, these weights are combined with the cluster scores based on geographic relevance. We evaluate our recommender on a large dataset collected from Panoramio consisting of the top-100 most populated cities in the world and show that incorporating the proposed temporal weighting function improves recommendation quality.